Simulation study on airflow in indoor environment with user-defined function - Tan, Jun Jie (2017)
In a typical building, half of the total energy consumption are consumed by the Heating, Ventilating and Air-Conditioning (HVAC) systems. HVAC systems provide heating, cooling and remove contaminated air to maintain the occupants’ thermal comfort and the indoor air quality (IAQ). The use of energy is efficiently utilized through well-designed HVAC systems. With the use of Computational Fluid Dynamics (CFD), the expected flow in rooms and buildings is simulated. The purpose of this project is to obtain an optimal airflow pattern with an occupant in the room using User-Defined Function (UDF). This study utilizes the software, ANSYS/FLUENT to simulate the ventilation in a 2-Dimensional (2D) room and analyzes the airflow patterns. An occupant is added in the room at three locations to investigate on the difference in the airflow pattern. Comparison of the airflow patterns between different configurations are displayed. Reversible and Irreversible UDF are applied and various effects are shown in each of the cases. The results are collected and discussions are made to determine the better configuration between the cases as well as the suitable type of UDF to be used in the cases. It is found that Irreversible UDF yields better thermal comfort when the inlet and outlet are on the same wall or when the outlet is near to the inlet. Reversible UDF is more suitable for rooms where the outlet is on the opposite wall or further from the inlet. When the occupant is located near the inlet, Reversible UDF works better for both cases. The findings in this project are valuable for real-life applications.